Molecular designing of high‐performance 3D star‐shaped electron acceptors containing a truxene core for nonfullerene organic solar cells. (12th August 2020) - Khan, Muhammad Usman; Mehboob, Muhammad Yasir; Hussain, Riaz; Fatima, Rafia; Tahir, Muhammad Suleman; Khalid, Muhammad; Braga, Ataualpa Albert Carmo
Abstract: End‐capped modification is a convenient strategy to enhance the photovoltaic and electronic properties of fullerene‐free acceptor materials. In this report, five novel star‐shaped three‐dimensional acceptor molecules FH1–FH5 are designed by end‐capped modifications of recently synthesized star‐shaped Tr (Hex)6 ‐3BR molecule. The enhancement in the photovoltaic, electronic, and photophysical properties of designed molecules is examined with the aid of density functional theory (DFT) and time‐dependent DFT (TDDFT). The MPW1PW91 functional in conjunction with 6‐31G(d, p) basis set of DFT/TDDFT is employed in order to compute various key parameters including frontier molecular orbitals analysis, absorption maxima, and binding energy along with transition density matrix, open‐circuit voltage, excitation energy, charge mobilities (electron and hole reorganizational energies), density of states, charge transfer with respect to HOMOPTB7‐Th –LUMOacceptor, and dipole moment. Red shifting in absorption spectra of acceptor materials is the most important reason for increasing efficiency of organic solar cells. A red shift in absorption spectra of all designed molecules is noted with low excitation energy. Designed molecules FH1–FH5 exhibit narrow energy gap with high electron mobility as compared with Tr (Hex)6 ‐3BR molecule. Among all designed molecules, FH4 is proved to be the best candidate for fullerene free organic solar cells because of narrow band gap, high charge mobility, high dipole moment, low excitation, and binding energy along with a red shift in absorption spectrum. Moreover, all designed molecules offer high current charge density as compared with Tr (Hex)6 ‐3BR. These results indicate that all star‐shaped conceptual molecules (FH1–FH5 ) are ideal aspirants for construction of future organic solar cells. Abstract : Five novel star‐shaped three dimensional (3D) acceptor molecules (FH1‐FH5) are designed by end‐capped modifications of recently synthesized star‐shaped Tr(Hex)6‐3BR molecule. The enhancement in the optoelectronic properties of designed molecules is examined using DFT and TDDFT calculations and compared with reference (R) acceptor molecule Tr(Hex)6‐3BR. Designed molecules exhibit better photovoltaic properties than Tr(Hex)6‐3BR molecule. Thus, star‐shaped conceptual molecules (FH1‐FH5) are ideal aspirants for construction of future organic solar cells. Highlights: Five novel star‐shaped three‐dimensional acceptor molecules FH1–FH5 are designed by end‐capped modifications of recently synthesized star‐shaped Tr (Hex)6 ‐3BR molecule. The enhancement in the photovoltaic, electronic, and photophysical properties of FH1–FH5 is examined through density functional theory and time‐dependent density functional theory. Designed molecules FH1–FH5 exhibit narrow energy gap and better photovoltaic properties with high electron mobility as compared with Tr (Hex)6 ‐3BR molecule. All star‐shaped conceptual molecules (FH1–FH5 ) are ideal molecules for construction of future organic solar cells.